2022
DOI: 10.3390/cancers14153601
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Neutropenia in Cancer Patients with Septic Shock: A 2009–2017 Nationwide Cohort Study

Abstract: (1) Background: Neutropenia’s prognostic impact on mortality in cancer patients with septic shock remains controversial despite recent advances in cancer and sepsis management. This population-based, case–control study aimed to determine whether neutropenia could be related to an increase in short-term and long-term mortality. (2) Methods: This population-based, case–control study used data from the National Health Insurance Service of Korea. Adult cancer patients who presented to the emergency department with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Leukopenia (leukocytes < 1.00 × 10 9 cells/L) was independently associated with mortality for patients without haematological malignancy, but was not a risk factor among patients with haematological malignancy. Previous studies describing the impact of neutropenia on sepsis mortality have yielded conflicting results, possibly related to heterogeneity of included patients [ 29 ] However, a population based cohort study of 43,466 patients with cancer and septic shock in Korea reported lower mortality in those with neutropenia [ 30 ]. We used leukopenia of < 1.00 × 10 9 cells/L as a surrogate for neutropenia, and observed a significant interaction between the effect of leukopenia and the presence of haematological malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Leukopenia (leukocytes < 1.00 × 10 9 cells/L) was independently associated with mortality for patients without haematological malignancy, but was not a risk factor among patients with haematological malignancy. Previous studies describing the impact of neutropenia on sepsis mortality have yielded conflicting results, possibly related to heterogeneity of included patients [ 29 ] However, a population based cohort study of 43,466 patients with cancer and septic shock in Korea reported lower mortality in those with neutropenia [ 30 ]. We used leukopenia of < 1.00 × 10 9 cells/L as a surrogate for neutropenia, and observed a significant interaction between the effect of leukopenia and the presence of haematological malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings add to a growing body of evidence suggesting favorable prognosis in patients with neutropenic hematological malignancy compared to other neutropenic patients with sepsis [ 14 , 15 ]. A large cohort study performed in Korea reported lower mortality among hematology patients with neutropenic compared to nonneutropenic sepsis [ 11 ]. Neutropenia in patients with hematological malignancy is frequently a transient and predictable toxicity of cancer therapy and may be expected to resolve spontaneously or with growth factor administration.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, in cohorts of patients with haematological malignancies and BSI, neutropenia might not be a major determinant of short-term mortality anymore, particularly in critically ills [ 33 , 34 ]. Indeed, BSI during neutropenia might have similar [ 11 , 35 ] or even sometimes better outcomes [ 10 , 20 , 36 ] compared to those in non-neutropenic patients, in particular if neutropenia is of short duration [ 3 ] and in the absence of metastatic localisation of infection, but rather in the context of transient bacteraemia [ 20 , 21 , 32 ]. BSI in neutropenic patients may also have better or comparable outcomes when compared to BSI in highly comorbid non-neutropenic patients [ 10 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%